Розширення шрифтів зі збереженням стилістики за допомогою генеративних змагальних мереж - Тимошенко , Павло Олександрович (Національний університет “Львівська політехніка”, 2023)
Магістерська кваліфікаційна робота виконана студентом групи КНСШ-21 Тимошенком Павлом Олександровичем. Тема «Розширення шрифтів зі збереженням стилістики за допомогою генеративних змагальних мереж». Робота направлена на здобуття ступеня магістр за спеціальністю 122 «Комп’ютерні науки». Об’єктом дослідження є процес автоматизації генерування шрифтів за допомогою трансформацій, створення на основі певних ознак та заданих прикладів. Предметом дослідження є генеративна модель машинного навчання, яку можна використовувати для вирішення поставленої проблеми. Досягнення поставленої мети відбувається використанням готової моделі, пристосованої для використання з латиницею та кириличним алфавітами. Для цієї моделі здійснено ґрунтовний препроцесинг даних: зібрано доступні шрифті в TTF та OTF форматах, досліджено спосіб перетворення їх у дані, які можна передати генеративній змагальній мережі. У результаті виконання дипломної роботи створено гібридну систему обчислювального інтелекту; розроблено її програмну реалізацію, яка дозволяє користувачу взаємодіяти з моделлю за допомогою GUI, «на льоту» здійснює попередню обробку даних, завантажених користувачем а також повертає результат моделі. Програмну імплементацію роботи опубліковано у репозиторії https://github.com/mitlyn/Fonty. Загальний обсяг роботи: 65 сторінок, 20 рисунків, 36 посилань. Throughout the existence of the printing industry, a huge number of fonts have been created. With the proliferation of pixel displays, the need for fonts has increased even more, because they are the only way to display textual information, the amount of which is increasing. User requirements for fonts have also grown over time - we would like to have fonts that are easy to read, print, reproduce handwritten forms, convey a certain mood, help create an image or brand, help encourage others, sell certain ideas, etc. The best of typefaces is now used everywhere in print and graphic design, and are taken for granted. The goal of this research is to automate the creation of fonts using artificial intelligence models. A computer can help create a huge number of fonts that would otherwise have to be drawn by hand. The purpose of the work is to automate the creation of fonts using artificial intelligence models. Such models can help create a huge number of fonts that would otherwise have to be drawn by hand. The novelty of this research lies in the fact that most of such works have been done mainly for the expansion of fonts within the Chinese hieroglyphic script, very few works investigate the problem of cross-language conversion, among them there are almost no works investigating the Latin script itself, and there are no relevant studies concerning Cyrillic. Cyrillic writing is very different from hieroglyphic writing, and the methods used to process it will vary accordingly. An analysis of already existing approaches is also presented in this study. The object of this study is the process of automating the generation of fonts using transformations, creation based on certain features and given examples. The subject of research is a generative model of machine learning that can be used to solve the given problem. The research methods are machine learning algorithms used to work with images. The total volume of work: 65 pages, 20 figures, 36 references.
Keywords: генерація шрифтів, генеративні моделі, машинне навчання, font generation, generative models, machine learning